The optically powerful quasar E1821+643 is associated with a 300 kiloparsec-scale FR I radio structure - Blundell, K; Rawlings, S (2001)
We present a deep image of the optically powerful quasar E1821+643 at 18 cm made with the Very Large Array. This image reveals radio emission, over 280 h-1 kpc in extent, elongated way beyond the quasar's host galaxy. Its radio structure has decreasing surface brightness with increasing distance from the bright core, characteristic of FR I sources. Its radio luminosity at 5 GHz falls in the classification for "radio-quiet" quasars (it is only 1023.9 W Hz-1 sr-1). Its radio luminosity at 151 MHz (which is 1025.3 W Hz-1 sr-1) is at the transition luminosity observed to separate FR I and FR II structures. Hitherto, no optically powerful quasar had been found to have a conventional FR I radio structure. For searches at low frequency, this is unsurprising given current sensitivity and plausible radio spectral indices for radio-quiet quasars. We demonstrate the inevitability of the extent of any FR I radio structures being seriously underestimated by existing targeted follow-up observations of other optically selected quasars, which are typically short exposures of z > 0.3 objects, and we discuss the implications for the purported radio bimodality in quasars. The nature of the inner arcsecond-scale jet in E1821+643, together with its large-scale radio structure, suggest that the jet axis in this quasar is precessing (cf. Galactic jet sources such as SS 433). A possible explanation for this is that its central engine is a binary whose black holes have yet to coalesce. The ubiquity of precession in radio-quiet quasars, perhaps as a means of reducing the observable radio luminosity expected in highly accreting systems, remains to be established. © 2001. The American Astronomical Society. All rights reserved.